2019
DOI: 10.1177/0269216319865414
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of barriers and enablers to the delivery of palliative care by primary care practitioners

Abstract: Background: There is increasing demand for primary care practitioners to play a key role in palliative care delivery. Given this, it is important to understand their perceptions of the barriers and enablers to optimal palliative care, and how commonly these are experienced. Aim: To explore the type and prevalence of barriers and enablers to palliative care provision reported by primary care practitioners. Design: A systematic review of quantitative data-based articles was conducted. Data sources: Medline, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 50 publications
4
75
0
9
Order By: Relevance
“…15 Primary care providers find it difficult to support their patients and appropriately initiate palliative efforts without sufficient information from secondary care and hospitals, especially when their AHF patients depend so significantly on the guidance of a cardiologist. 21 The Miseducation of PC One of the most significant barriers to palliative referrals for AHF patients is the misperception that PC is a service reserved for those patients near death. 5 While some providers use increased symptom burden, functional decline, and events such as device implantation or heart transplant as triggers to make PC referrals for their AHF patients, Kavalieratos and colleagues show that it is frequently the practice of providers to use the "'point at which you are unable to do more'" as the driving trigger for PC referral.…”
Section: Cracks In Communicationmentioning
confidence: 99%
“…15 Primary care providers find it difficult to support their patients and appropriately initiate palliative efforts without sufficient information from secondary care and hospitals, especially when their AHF patients depend so significantly on the guidance of a cardiologist. 21 The Miseducation of PC One of the most significant barriers to palliative referrals for AHF patients is the misperception that PC is a service reserved for those patients near death. 5 While some providers use increased symptom burden, functional decline, and events such as device implantation or heart transplant as triggers to make PC referrals for their AHF patients, Kavalieratos and colleagues show that it is frequently the practice of providers to use the "'point at which you are unable to do more'" as the driving trigger for PC referral.…”
Section: Cracks In Communicationmentioning
confidence: 99%
“…Finally, it is important to note that our findings do not mean that no literature on out-of-hours palliative care exists, simply that evaluations specifically were not identified. Our review identified, but did not include as eligible, topics including general practitioner perspectives on out-of-hours palliative care 48,49 ; pilot programmes on, inter alia, prescribing and telehealth 50,51 ; and an ongoing systematic review to identify quality improvement projects in out-of-hours palliative care 52 . These studies and others advance understanding outside of our evaluative focus, as well as potentially improving future evaluative studies.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this review2 was to explore the types and frequency of barriers and enablers to palliative care provision, as reported by practitioners. The authors conducted a systematic review of observational studies following the Joanna Briggs Institute (JBI)3 manual.…”
Section: Methodsmentioning
confidence: 99%